Influence of Irrigation and Water Use on the Agronomic Traits of Crops - Ruoshui Wang; Yuguo Han; Tibin Zhang; Qibiao Han (Agronomy)
Water scarcity is a significant challenge to the sustainable development of agriculture [...]